Electrothermal AAS determination of Ni in soft drinks using Co as the internal standard - De Oliveira, Adriana Paiva [UNESP]; Gomes Neto, José Anchieta [UNESP]; Nóbrega, Joaquim A.; Oliveira, Pedro Vitoriano (My University, 2005)
A method for the direct determination of Ni in soft drinks by graphite furnace atomic absorption spectrometry using a transversely heated graphite atomizer (THGA), Zeeman-effect background corrector, and Co as the internal standard (IS) is proposed. Magnesium nitrate was used to stabilize both Ni and Co. All diluted samples (1+1) in 0.2% (v/v) HNO3 and reference solutions [5.0-50 μg L-1 Ni in 0.2% (v/v) HNO3] were spiked with 50 μg L-1 Co. For a 20-μL, sample dispensed into the atomizer, correlations between the ratio of absorbance of Ni to absorbance of Co and the analyte concentration were close to 0.9996. The relative standard deviation of the measurements varied from 0.5 to 3.4% and 1.0 to 7.0% (n=12) with and without IS, respectively. Recoveries within 98-104% for Ni spikes were obtained using IS. The characteristic mass was calculated as 43 pg Ni and the limit of detection was 1.4 μg L-1. The accuracy of the method was checked for the direct determination of Ni in soft drinks and the results obtained with IS were better than those without IS.